Phytochemical Screening and Antibacterial Activity of Aqueous and Ethanolic Extracts from Marrubium Vulgare L Plant - Ashkorfo, Salma Abdusalam Ali; Al-mabrook, Selima Ali Mohammed; Edrah, Salem Mohamed (Scientific Journal for Faculty of Science-Sirte University, 2024)
Marrubium vulgare L., a remarkable medicinal herb, has been used for centuries to effectively treat various ailments, including coughs, colds, and digestive issues. Renowned for its expectorant, diaphoretic, and anti-inflammatory properties, this precious herb has become a cornerstone of traditional medicine worldwide. In this study, the productivity of the ethanolic extract was an impressive 33.69%, while the aqueous extract showcased a still remarkable 14.5%. The pH levels demonstrated the ethanolic extract at 4.02 and the aqueous extract at 6.61. Phytochemical screening revealed the presence of beneficial compounds such as alkaloids, flavonoids, saponins, phenols, steroids, and terpenes in both extracts. It is noteworthy that the ethanolic extract exhibited a higher presence of tannins, which were not found in the aqueous extract. In contrast, the ethanolic extract did not contain phenols, whereas the aqueous extract contained a significant amount of these compounds. To further explore the biological potential of these extracts, this study was conducted on their activity against E. coli and S. aureus. The findings revealed that the aqueous extract’s astounding inhibition zones, measured at 19 mm and 17 mm against E. coli and S. aureus respectively. The ethanolic extract also exhibited noteworthy results, with inhibition zones of 16 mm and 18 mm against E. coli and S. aureus correspondingly. Clearly, Marrubium vulgare L. is a truly remarkable herb with immense medicinal value.